2023
DOI: 10.3390/land12040926
|View full text |Cite
|
Sign up to set email alerts
|

Weed Seed Banks in Intensive Farmland and the Influence of Tillage, Field Position, and Sown Flower Strips

Abstract: Agricultural intensification has caused once diverse arable fields to become species-poor. Their seed banks, which are fundamental for re-establishment and maintenance of plant communities in such repeatedly disturbed environments, are now largely depleted. In order to advise farmers on the successful implementation of agri-environmental measures, as well as reduce potential subsequent costs of continued weed control, understanding seed bank dynamics in relation to aboveground vegetation is essential. We (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…As previously observed in the literature, RT increases the seedling density of seedbank on the upper soil layer compared with CT. However, the quantity of weed seedling within soil depth 10-25 cm was found to not be statistically different between CT and RT, which result is in line with other studies (Cardina et al, 2002;Schnee et al, 2023). This effect was confirmed independently for the two dominant weeds (ALOMY and MATCH).…”
Section: Impact Of Soil Management On Weed Densitysupporting
confidence: 90%
See 1 more Smart Citation
“…As previously observed in the literature, RT increases the seedling density of seedbank on the upper soil layer compared with CT. However, the quantity of weed seedling within soil depth 10-25 cm was found to not be statistically different between CT and RT, which result is in line with other studies (Cardina et al, 2002;Schnee et al, 2023). This effect was confirmed independently for the two dominant weeds (ALOMY and MATCH).…”
Section: Impact Of Soil Management On Weed Densitysupporting
confidence: 90%
“…These differences are mainly explained by complex interactions with other factors such as: differences in the duration of the experiment, the history of the field, and the species present (Nichols et al, 2015). However, it is commonly reported that reducing tillage increases weed density and favours grass populations (Nichols et al, 2015;Schnee et al, 2023;Travlos et al, 2018;Trichard et al, 2013). On the other hand, residue restitution can influence weed dynamics by changing nutrient dynamics, soil temperature or soil moisture (Liebman and Mohler, 2001;Nichols et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Promising are the diversification of crop plants to increase biodiversity by crop rotation, simultaneous sewing of various crops on the same field, or intercropping [3,9,30,46]. These methods are also beneficial for soil quality and could thereby reduce the need for tillage that can also lower biodiversity [52]. NPA should be interconnected to form functional connectivity between populations.…”
Section: Recommendations For Effective Insect Conservation In Nature ...mentioning
confidence: 99%